Differentiation of design solutions according to architectural and artistic criteria - Ziyatdinov Zufar Z. (Архитектон)
The paper proposes a classification of buildings and structures into levels by the criterion of whether their design solutions contain such architectural and artistic qualities as architectural idea, artistic image and integrity of architectural composition. In total, four levels of construction have been identified. At the lower first level, the utilitarian-functional approach prevails, where the shell of the building body strictly follows the function and carries no artistic meaning. The second level is decoration or embellishment, when patterns, mantles and decor are superimposed on the object. At the next level, work concerns the form: the exterior express the units or program, cantilevered spaces, offset volumes (left-right, up-down, forward-inwards), various surface finishes. The highest level is when the volume conveys an architectural idea, an artistic idea, and all the composition techniques and means work to reveal it.